2017
DOI: 10.1111/ajco.12663
|View full text |Cite
|
Sign up to set email alerts
|

What does it cost Medicare to diagnose and treat men with localized prostate cancer in the first year?

Abstract: The costs of treating and managing prostate cancer are high and these result in a substantial financial burden for the Australian MBS. Costs attributable to prostate cancer appear to vary widely based on initial treatment and these are likely to increase with the introduction of more expensive services and pharmaceuticals. There is a pressing need for better prognostic tools to distinguish between indolent and aggressive prostate tumors to reduce potential over treatment and help ease the burden of prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…2 The worst effects of financial stress are termed 'financial toxicity', 3,4 which is measured through monetary (absolute costs accrued by the patient), objective (methods used to ease financial burden) and subjective (perceived financial burden) measures. 2 Although some researchers and clinicians are attempting to incorporate price transparency into conversations with patients, 5,6 the effects of cancer costs remain an issue of growing importance, [7][8][9][10] and are a primary issue that Australian health consumers and cancer patient organisations have identified requiring further action. [11][12][13] To support health services and policy makers to address their concerns, a model or framework underpinning the patient experiences in a public-private setting would contribute towards identifying areas to target and address.…”
Section: Introductionmentioning
confidence: 99%
“…2 The worst effects of financial stress are termed 'financial toxicity', 3,4 which is measured through monetary (absolute costs accrued by the patient), objective (methods used to ease financial burden) and subjective (perceived financial burden) measures. 2 Although some researchers and clinicians are attempting to incorporate price transparency into conversations with patients, 5,6 the effects of cancer costs remain an issue of growing importance, [7][8][9][10] and are a primary issue that Australian health consumers and cancer patient organisations have identified requiring further action. [11][12][13] To support health services and policy makers to address their concerns, a model or framework underpinning the patient experiences in a public-private setting would contribute towards identifying areas to target and address.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is one of the highest increasing cancers in terms of medical costs with a tremendous economic burden (Norlund et al, 2003;Fourcade et al, 2010;Felix et al, 2011;Mariotto et al, 2011;Luengo-Fernandez et al, 2013;Mervin et al, 2017;Restelli et al, 2017;Satoh et al, 2018;Zhuo et al, 2019). Previous studies have shown that metastatic progression contributed to an increase in costs and medical resource use for prostate cancer patients (Penson et al, 2004;Li et al, 2017;Satoh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Being older at diagnosis and higher comorbidity would affect treatment choice of prostate cancer patients and be associated with increased costs (Wilson et al, 2007;Krahn et al, 2010). Studies on the economic burden or costs of prostate cancer were mainly focused on the United States, Europe countries (Sanyal et al, 2013;Smith-Palmer et al, 2019), or other developed countries (Grover et al, 1999;Grover et al, 2000;Krahn et al, 2010;Kitazawa et al, 2015;Mervin et al, 2017;Satoh et al, 2018). Only a few studies described the medical expenditure of Chinese patients with metastatic prostate cancer and presented a high prevalence of bone metastasis among Chinese prostate cancer patients (Qian et al, 2019;Zhuo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%